2021
DOI: 10.1002/agt2.147
|View full text |Cite
|
Sign up to set email alerts
|

Color‐tunable and bright nonconjugated fluorescent polymer dots and fast photodegradation of dyes under visible light

Abstract: Nonconjugated polymer dots (PDs) without largely conjugated structures entitle their advantages such as environment friendliness, nontoxicity, and intrinsic fluorescence. However, color-tunable PDs remain a challenge. Herein, polyvinyl pyrrolidone (PVP) and ascorbic acid (AA) are used to synthesize nonconjugated PDs, namely, PA PDs with intensive blue emission. The introduction of a third component, m-phenylenediamine (MPD), redshifted the emission to green. The asprepared color-tunable blue to green emissive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Additionally, NCPs could function as effective CTMs, primarily hole transport materials (HTM) in organic electronic devices like solar cells and light-emitting diodes . Their presence enhances charge extraction and efficient transport.…”
Section: Application Of Ncps In Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, NCPs could function as effective CTMs, primarily hole transport materials (HTM) in organic electronic devices like solar cells and light-emitting diodes . Their presence enhances charge extraction and efficient transport.…”
Section: Application Of Ncps In Pscsmentioning
confidence: 99%
“…Additionally, NCPs could function as effective CTMs, primarily hole transport materials (HTM) in organic electronic devices like solar cells and light-emitting diodes. 31 Their presence enhances charge extraction and efficient transport. Moreover, certain NCPs can function as effective barrier materials, safeguarding against the influence of moisture, oxygen, and other environmental factors.…”
Section: Application Of Ncps In Pscsmentioning
confidence: 99%
“…These materials commonly feature nonconjugated structures, and through-space interactions were proposed as the key attribute governing luminescence within this material class. They often exhibit clusterization-triggered emission (CTE) behaviors, the phenomenon termed “clusteroluminescence”. , Accordingly, polymerization represents an effective approach for achieving NTIL/CTE properties while affording control over color tunability . This strategy, coined polymerization-induced emission, provides a new perspective for generating emissive polymers from unconventional and initially nonemissive groups …”
Section: Key Concepts In the Recent Design Of Fluorescent Polymersmentioning
confidence: 99%
“…30 It has also been shown that alkyl chain-dependent microstructures and self-assembled aggregates produce various emission colors in solution. [31][32][33][34][35][36][37] The fabrication of luminescent materials with adjustable emission color by self-assembly of p-conjugated molecules has attracted particular attention. In the literature, 38 a thiophene-based a-cyanostyrene derivative was observed to form nanoparticles with a bright fluorescence when self-assembled by adding water to an organic solution (THF or DMSO).…”
Section: Introductionmentioning
confidence: 99%